Impact of Glucagon-like Peptide-1 Receptor Agonists on Intestinal Epithelial Cell Barrier - Takizawa Y.; Kato A.; Onsui A.; Kanatanai S.; Ishimura A.; Kurita T.; Nakajima T. (Sciendo, 2024)
While many types of diabetes medications are currently available, orally administered formulations of glucagon-like peptide-1 (GLP-1) receptor agonists have recently been launched. Therefore, gastrointestinal epithelial cells will be increasingly exposed to GLP-1 receptor agonists; however, their effects on these cells remain unclear. The present study attempted to clarify the effects of GLP-1 receptor agonists on intestinal epithelial barrier functions. Semaglutide (5, 50, and 500 ng/mL) and dulaglutide (15, 150, and 1500 ng/mL) were selected as GLP-1 receptor agonists and applied to the Caco-2 cell line. Changes in mRNA and protein expression levels of epithelial cell barrier regulators due to exposure to GLP-1 receptor agonists were examined by real-time RT-PCR and Western blotting. Neither semaglutide nor dulaglutide changed the growth rate or ratio of Caco-2 cells. Furthermore, they did not significantly affect the mRNA expression levels of membrane proteins involved in epithelial cell barrier functions. However, dulaglutide increased the protein expression levels of these membrane proteins in a concentration-dependent manner, whereas semaglutide did not. Only dulaglutide enhanced epithelial cell barrier functions. Since various gastrointestinal symptoms develop in patients with diabetes and epithelial cell barrier functions may be compromised, medicines that promote barrier function, such as dulaglutide, may effectively attenuate these changes. However, their mechanisms of action remain unknown; therefore, further studies are warranted.